2011
DOI: 10.1108/09596111111153501
|View full text |Cite
|
Sign up to set email alerts
|

Complex and chaotic tourism systems: towards a quantitative approach

Abstract: Tourism systems have been considered more and more in the light of complexity and chaos theories. Most of the work done in this area has highlighted the reasons and the issues for this approach. A steadily growing strand of the recent literature uses it to overcome the problems of a reductionist and mechanicistic view considered unable to provide a full understanding of the structural and dynamic characteristics of tourism systems and specifically of tourism destinations. This paper continues this approach and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 83 publications
3
88
0
4
Order By: Relevance
“…'Bifurcation' is closely related to the 'edge of chaos' and refers to the situation where the system overwhelms a critical point of the space phase and moves in a new phase (Baggio and Sainaghi, 2011). Through bifurcation, the values of a system's parameters can experience significant unexpected change.…”
Section: The Chaos Theory Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…'Bifurcation' is closely related to the 'edge of chaos' and refers to the situation where the system overwhelms a critical point of the space phase and moves in a new phase (Baggio and Sainaghi, 2011). Through bifurcation, the values of a system's parameters can experience significant unexpected change.…”
Section: The Chaos Theory Perspectivementioning
confidence: 99%
“…Hence, 'selforganisation' is the consequence of bifurcation where order re-emerges out of a random and chaotic phase (Sellnow et al, 2002). Baggio and Sainaghi (2011) argue that through 'selforganisation' the system becomes more 'suitable' to deal with external or internal obstacles because of more optimised available resources. Paraskevas (2006) adds that 'self-organisation' is actually the spontaneous reallocation of energy that occurs in response to the perceptions of each system's components (agents) rather than through some principal controlling mechanism.…”
Section: The Chaos Theory Perspectivementioning
confidence: 99%
“…Reference approach: (Baggio et al, 2011;Bhattacharya et al, 2014;Huang, 2009;Wu et al, 2009;Kaplan & Norton, 1992;Malina et al, 2001;Martinsons et al, 1999;Mehrdad et al, 2013;Tseng, 2010;Naranjo et al, 2009;Nikzadet et al, 2011;Ratnasingam, 2014;and Sabah et al, 2012).…”
Section: Perspective Of Internal Business Processmentioning
confidence: 99%
“…This effective decision included combining four perspective steps of BSC that focused on a system with different behaviors. (Kaplan & Norton, 1996b) created the BSC method with the concept of causality so that researchers having BSC mindset can be synergized with SEM, using large enough data to support it (Baggio and Sainaghi, 2011). The previous research has suggested that customers and financial performance are causally related to each other (Nielsen, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Literature review reveals that system theory is applied to various elds of science: in cybernetics (Kljajić, 1994), mathematics, biology (Maturana and Varela, 1998) and also in tourism (Jere Lazanski, 2009); particularly in connection with tourism systems (Leiper, 1990;Baggio and Sainaghi, 2011;Baggio, 2013); tourist destination (Vodeb, 2010); a system of sustainable development (McDonald, 2009;Stubelj and Bohanec, 2010;Nguyen et al, 2011;Camus et al, 2012), as an approach to innovation (Mulej, 1994;Mulej and Ženko, 2002); or otherwise like a systemic perspective to the management ideas (Fatur and Likar, 2009;Ropret et al, 2014) and so on.…”
Section: Introductionmentioning
confidence: 99%